Analyzing and Measuring the Impact of the Digital Economy on International Trade, the Case of Jordan for the Period (1990-2020) - Al-Badrany, Ali Sattm Sultan; Al-Din Al-Khatib, Rabah Jamil Saad (Integrated Journal for Research in Arts and Humanities, 2023)
The digital economy is defined as the economy that relies mainly on the economics of information and informatics technology that is based on digital technology. The sectors of information, communication and informatics technology have become one of the most important sectors driving economic growth in the developed countries now, because of the great potential they contain in various fields of the modern economy. The research aims to study the impact of the digital economy on international trade. Descriptive, as a general introduction to the various concepts of the digital economy and its role in international trade, as well as relying on the statistical quantitative analytical approach to analyze the results obtained. The research concluded many results and proposals.